2019
DOI: 10.3390/polym11091404
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Performance of Polymer-Modified Asphalt Mixes: Preliminary Evaluation of the Usefulness of Standard Technical Index in Polymer-Modified Asphalt

Abstract: The objectives of this study are to evaluate the high-temperature performance of polymer-modified asphalt and asphalt mixtures, and to investigate if the standard technical indexes are useful in the performance evaluation of the polymer-modified asphalt. There are four typically used polymer-modified asphalt types employed in the study. The standard high-temperature rheological test, such as the temperature sweep test, was used to express the high-temperature performance of the polymer-modified asphalt. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Asphalt binders can be made harder by modification. Different types of modifiers were tried worldwide to enhance the rheological properties of asphalt binder, such as polymers [1][2][3][4][5][6], crumb rubber [5,[7][8][9][10][11], waste plastic [12][13][14][15][16], geopolymers [17], and nano-materials [18][19][20][21]. Polymers are commonly used to modify and improve the rheological properties of asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asphalt binders can be made harder by modification. Different types of modifiers were tried worldwide to enhance the rheological properties of asphalt binder, such as polymers [1][2][3][4][5][6], crumb rubber [5,[7][8][9][10][11], waste plastic [12][13][14][15][16], geopolymers [17], and nano-materials [18][19][20][21]. Polymers are commonly used to modify and improve the rheological properties of asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the effect of using modifiers on asphalt binder and mixture properties. The results of these studies showed that polymer modification could alter binder properties by increasing the softening point [ 1 , 2 , 3 , 4 , 14 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], increasing the viscosity [ 3 , 37 , 39 , 40 ], decreasing the penetration [ 2 , 3 , 14 , 37 , 38 ], and improving the performance grade [ 2 , 4 , 6 , 37 , 41 ]. For asphalt mixture, the previous studies indicated that polymers could improve the mechanical properties of asphalt mixture, such as resilient modulus [ 14 , 42 , 43 , 44 , 45 , 46 ], fatigue cracking resistance [ 4 , 14 , 47 , 48 , 49 , 50 , 51 ], and rutting resistance [ 43 , 50 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterize the rutting resistance of asphalt more accurately, new parameters such as Sheony parameter, zero shear viscosity (ZSV), and unrecoverable creep compliance are proposed. Among them, the unrecoverable creep compliance obtained by multiple stress creep recovery (MSCR) test is considered to be able to evaluate the rutting resistance potential of asphalt [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This method involves the crushing of the material that is to be used into very small sizes and carefully blending with heated bitumen to ensure proper homogenous mixing. The existing literature includes the utilization of polymers, such as end-of-life tires (ELTs), high-density polyethylene (HDPE), low-density polyethylene (LDPE), polymerizing vinyl chloride (PVC), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile butadiene styrene (PET), and silicon resin polymers [4,[6][7][8][9]. In the case of dry mixing, the modifier is introduced and transferred to the mixer with aggregates and pure bitumen (unmodified).…”
Section: Introductionmentioning
confidence: 99%